2022
DOI: 10.3390/ijms23126520
|View full text |Cite
|
Sign up to set email alerts
|

The Unfolded Protein Response Sensor PERK Mediates Stiffness-Dependent Adaptation in Glioblastoma Cells

Abstract: Glioblastoma multiforme (GBM) is the most aggressive brain tumor in adults. In addition to genetic causes, the tumor microenvironment (TME), including stiffening of the extracellular matrix (ECM), is a main driver of GBM progression. Mechano-transduction and the unfolded protein response (UPR) are essential for tumor-cell adaptation to harsh TME conditions. Here, we studied the effect of a variable stiff ECM on the morphology and malignant properties of GBM stem cells (GSCs) and, moreover, examined the possibl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 59 publications
2
11
0
Order By: Relevance
“…On the other hand, disruption of F-Actin polymerization by Latrunculin B treatment also impaired stiffness dependent adaptation of GG16-WT cells, and strongly reduced GFAP expression thus mimicking the PERK-KO phenotype (Supplementary Figure S1). As controls, stiffness dependent increases of FLNA and F-Actin seen in WT cells was disrupted in PERK deficient cells (Supplementary Figure S2 and S3), in agreement with our earlier findings [35].…”
Section: Resultssupporting
confidence: 92%
See 3 more Smart Citations
“…On the other hand, disruption of F-Actin polymerization by Latrunculin B treatment also impaired stiffness dependent adaptation of GG16-WT cells, and strongly reduced GFAP expression thus mimicking the PERK-KO phenotype (Supplementary Figure S1). As controls, stiffness dependent increases of FLNA and F-Actin seen in WT cells was disrupted in PERK deficient cells (Supplementary Figure S2 and S3), in agreement with our earlier findings [35].…”
Section: Resultssupporting
confidence: 92%
“…Recently, we reported that the endoplasmic reticulum (ER) stress and unfolded protein response (UPR) sensor PKR-like ER kinase (PERK) mediates an adaptive cellular response in GSCs towards increasing substrate/ECM stiffness mimicked by stiffness tunable hydrogels [35]. PERK is known to have both a kinase function and a protein scaffold function by which it regulates a number of cellular processes that have been related either to restoring proteostasis, or to regulate F-Actin remodeling in order to facilitate ER – cell membrane interaction for maintaining calcium homeostasis [36,37].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Nevertheless, in certain circumstances, GBM may experience immune flight through not rendering neoplastic antigens or MHC-1, thereby blocking recognition by CD8-positive T-cells ( 42 , 43 ). EIF2AK3, best known as PERK, was reported to promote glioma cell viability, migration, and anti-apoptosis in vitro ( 44 , 45 ). Our in vitro experiments also confirmed that the expression level of EIF2AK3 elevated with an increase in tumor grade, and EIF2AK3 enhances the abilities of tumor cell proliferation and migration.…”
Section: Discussionmentioning
confidence: 99%